Pendidikan Karakter dalam Komik Si Toyeb Karya Husni Assaerozi - Hayati Wahyuni, Hayati; Bahanan, Mochamad Abduloh (Mahad Aly Al Fithrah, 2021)
In constitution Number 20 of 2003 year Chapter 2 Article 3 talking about the national education system said that